Human blood platelets lack nitric oxide synthase activity. (September 2015) - Böhmer, Anke; Gambaryan, Stepan; Tsikas, Dimitrios
Abstract Reports on expression and functionality of nitric oxide synthase (NOS) activity in human blood platelets and erythrocytes are contradictory. We used a specific gas chromatography–mass spectrometry (GC–MS) method to detect NOS activity in human platelets. The method measures simultaneously [15N]nitrite and [15N]nitrate formed from oxidized 15N-labeled nitric oxide (15NO) upon its NOS-catalyzed formation from the substrate l-[guanidino-15N2]-arginine. Using this GC–MS assay, we did not detect functional NOS in non-stimulated platelets and in intact platelets activated by various agonists (adenosine diphosphate, collagen, thrombin, or von Willebrand factor) or lysed platelets. l-[guanidino-nitro]-Arginine-inhibitable NOS activity was measured after addition of recombinant human endothelial NOS to lysed platelets. Previous and recent studies from our group challenge expression and functionality of NOS in human platelets and erythrocytes.